2008
DOI: 10.1089/lap.2007.0071
|View full text |Cite
|
Sign up to set email alerts
|

Totally Extraperitoneal Laparoscopic Inguinal Hernia Repair Is a Safe Option in Patients with Previous Lower Abdominal Surgery

Abstract: TEP repair is feasible in patients with previous lower abdominal surgery. TEP was planned as a day-case procedure; however, patients with recurrent hernias needed a planned admission, as an overnight stay was required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
1
12
1
Order By: Relevance
“…The two groups were well matched and had sufficient numbers of patients. The groups were comparable in terms of both surgical outcomes and conversions/complications, which were acceptable compared with those of other studies [10][11][12][13].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The two groups were well matched and had sufficient numbers of patients. The groups were comparable in terms of both surgical outcomes and conversions/complications, which were acceptable compared with those of other studies [10][11][12][13].…”
Section: Discussionsupporting
confidence: 56%
“…Several researchers have reported that it is feasible for experienced hands to perform TEP hernia repair for patients with a previous lower abdominal operation [10][11][12]. The clinical setting of an inguinal hernia after previous lower abdominal surgery is not very frequent, precluding any attempt to conduct an ideal clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to enter the preperitoneal space after previous surgery and to perform dissection during a TEP hernia repair due to adhesion. There have been few studies on the feasibility of TEP hernia repair after PLAS [2][3][4][5][6]. Furthermore, there have been no reports on the feasibility and safety of SILS-TEP in patients with PLAS [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…). Of 11 full‐text articles assessed for eligibility, seven studies were included in the qualitative and quantitative data synthesis, involving a total of 1657 hernia repairs (PS 326, NS 1331). Studies excluded after full‐text review are summarized in Table S1 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…Previous lower abdominal surgery is often considered a relative contraindication to TEP repair, as access to the preperitoneal space may be challenging when scar tissue from previous interventions is encountered. Nonetheless, the feasibility and safety of TEP repair in patients with a history of lower abdominal surgery remains inconclusive. The aim of this study was to perform a meta‐analysis of trials comparing the feasibility and safety of TEP inguinal hernia repair in patients with (PS, previous surgery group) and without (NS, no previous surgery group) a history of lower abdominal surgery.…”
Section: Introductionmentioning
confidence: 99%